Faktor yang Mempengaruhi Kepatuhan Konsumsi Tablet Tambah Darah Pada Ibu Hamil - Siska; Yustati, Eva; Marita, Yulis (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Data from the World Health Organization (WHO), 15-20% of maternal deaths are directly or indirectly caused by anemia, on the other hand, anemia is also related to maternal morbidity. This study aims to determine the compliance factors for TTD consumption in pregnant women, using a cross sectional design. The population of pregnant women in Tanjung Enim Subdistrict is 81 pregnant women and a sample of 81 samples is needed using a simple random sampling technique. Univariate analysis results show that of the 81 respondents, 45 (55.6%) of TTD consumption compliance were non-compliant, 36 (44.4%) were compliant, 47 (58.0%) had poor knowledge, 34 (42.0%) had good knowledge. Negative attitudes 43 (53.1%), positive attitudes 38 (46.9%). Bivariate analysis chi square statistical test obtained a p value of 0.000, which means there is a significant relationship between knowledge and compliance with TTD consumption. The p value is 0.000 which means there is a significant relationship between attitude and compliance with TTD consumption. Conclusion there is a significant relationship between knowledge, attitudes and compliance with TTD consumption in pregnant women